Quality of Herbal Tea Combination Between Corn Silk and Mint Leaf in a Variation of Temperature and Drying Duration - Husna, Imroatul; Suryani, Titik (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Corn silk has high antioxidant activity so that with a combination of mint leaf it can be made into herbal tea which is beneficial for health. This research aims to determine the antioxidant activity and organoleptic quality of herbal tea combination between corn silk and mint leaf in a variations of temperature and drying duration. The method in this research used a completely randomized design (CRD) with 2 factors, factor 1 were drying temperature (J) (45 °C, 50 °C, and 55 °C) and factor 2 were drying time (K) (2 hours and 4 hours). The results of this study showed that the highest antioxidant activity of the herbal tea combination between corn silk and mint leaf on J₁K₂ treatment (temperature 45 °C and drying time 4 hours) of 85.375 %, while the best organoleptic quality of herbal tea between corn silk and mint leaf was in the J₁K₁ treatment (temperature of 45 °C and drying duration of 2 hours) with a fresh taste, mint tea aroma, and yellowish color.